The activity of trunk muscles in paraplegic patients after breaststroke initiation - de Witte, B.; Loyens, R.; Robeaux, R.; Clarys, J. P. (Swimming Science V, 1988)
Sport activities permit paraplegics to maintain the physical efficiency level that was obtained during medical rehabilitation, and they are the best way to improve efficiency because they allow a proper effort dosage (Pachalski & Mekarski, 1980). Swimming for the physically handicapped creates some problems, because differences in physical abilities depend upon individual handicaps, but swimming is an activity that lends itself to the disabled (Guttman, 1%5; Trussell, 1971). Earlier research (Duffield, 1973; Nicol, Schmidt-Hansberg, & McMillan, 1979; Paeth, 1984; Vis, 1971, 1975) showed the positive therapeutical effects for the handicapped of training in water. In the evolution of teaching swimming techniques, consideration must be given to the various needs and abilities of the handicapped so that they can control the movement of the asymmetrical body shapes (e.g., the Halliwick method). In this regard, no two individuals are alike. Many studies have been undertaken to gather information or to explain the teaching techniques in swimming with the handicapped. Persyn, Surmont, Wouters, and De Mayer (1975) stated that the individual solution for adequate movement in water is as variable as the possible differences in handicaps; therefore, it is difficult to develop norms. Some researchers recommend the use of a specific swimming technique for supporting or strengthening certain muscle groups. Very few of these recommendations are based on scientific experiences (Duffield, 1973; Lorenzen, 1970; Vis, 1971). Besides this, the experimental investigations on the function of muscles during swimming, especially the breaststroke, are limited to the able-bodied. Electromyography (EMG) of the breaststroke has been studied by Ikai, Ishii, and Miyashita (1964, 14 muscles); Lewillie (1971, 3 muscles; 1974; 2 muscles); Tokuyama, Okamoto, and Kumamoto (1976, 14 muscles); Yoshizawa, Tokuyama, Okamoto, and Kumamoto (1976, 16 muscles); and by Yoshizawa, Okamoto, Kumamoto, Tokuyama, and Oka (1978; 16 muscles). Maes, Clarys, and Brouwer (1975) related the EMG results of five muscles during the breaststroke to the "normal" and disabled swimmer. Persyn et al. (1975) concluded that the physically handicapped swimmer at the "Special Olympic" level often fails to receive adequate training from swimming experts. Considering the poor swimming technique among the best swimmers, the situation is probably much worse for the remaining handicapped persons. In order to set up a basic teaching program on swimming technique for paraplegics, instruction in the breaststroke was initiated for 4 patients with different levels of spinal cord injury. Based on the literature that the breaststroke is an effective way to develop back and shoulder muscles and the importance of these muscle groups for the paraplegic's general efficiency exercises, the participation level of trunk muscles during breaststroke was studied using telemetric EMG in the second phase of this study.